Efficacy of sarilumab and dexamethasone co-administration for lowering multiple blood biomarkers in the treatment of cytokine release syndrome in hospitalized covid-19 patients - Ishtiaq Ahmad; Hamidullah (Journal of the Pakistan Medical Association)
The current study was planned to explore the potential synergistic role of the co-administration of sarilumab and dexamethasone in reducing blood biomarkers associated with cytokine release syndrome in hospitalised patients of coronavirus disease-2019. The sample comprised 22 patients hospitalised with severe and critical severity levels and who were treated with sarilumab and dexamethasone. Positive responses were seen in blood biomarkers, including decreased interleukin-6 alpha levels and improved oxygen saturation. Tumour necrosis factor, D-dimer, C-reactive protein, ferritin and lymphocyte count also showed positive responses in patients who survived than those who died. Lactate dehydrogenase levels fluctuated with improvement among the survivors, but had limited effectiveness in those who died. The findings suggested promising avenues for future treatment strategies in patients with severe coronavirus disease-2019 and cytokine release syndrome.